Justice Beyond Rights: A Philosophical Inquiry into Intellectual Property Through Derrida’s Deconstruction - Darma, I Made Wirya; Kurniawan, I Gede Agus; Mahadnyani, Tjokorda Mirah Ary; Thapa, Nar Yan (Fakultas Syariah dan Hukum UIN Sunan Gunung Djati Bandung, 2025)
Intellectual property law, which aims to protect creators of intellectual works, faces significant jus-tice-related challenges in the context of globalisation and access inequality. These issues can be criti-cally examined through Jacques Derrida’s deconstruction approach, which reveals contradictions and limitations in the pursuit of substantive justice. This study aims to critique the legal conception of justice within intellectual property law (IPL) through Derrida’s philosophical framework of decon-struction and to examine the implications of applying this theory to the interpretation and imple-mentation of justice in IPL. This research employs a normative legal methodology with a conceptual approach, analysing primary, secondary, and tertiary legal materials through a literature study and applying qualitative data analysis techniques to assess the notion of justice in IPL through the lens of Derrida. The findings reveal normative contradictions and conceptual instabilities within the IPL system, particularly concerning foundational principles such as originality, exclusive rights, and intellectual ownership. By deconstructing the binary oppositions underlying IPL, the study reveals that exclusionary and biased legal structures frequently influence the application of justice principles in IPL. This study contributes to legal scholarship by advocating for a more inclusive and equitable legal framework that ensures access to knowledge, thereby opening up new interpretive possibilities in the discourse on justice within intellectual property law.